Publications on Post-Covid Mucormycosis: A Bibliometric Study of WHO Database. (Bangladesh Journal of Medical Science, 2021)
Background: The COVID-19 pandemic has triggered a large number of publications to inform, understand, conduct more research and control the situation. Although the researchers are analyzing the bibliometrics on this condition, no bibliometric studies are available on the publications related to post-covid mucormycosis. This study is aimed at bibliometric assessment of the publications related to post-covid mucormycosis.Methods: In the presented study, authors have performed the bibliometric analysis of the World health organization (WHO) database named ‘Global literature on coronavirus disease.’ WHO is maintaining this database since the pandemic, and it contains thousands of reports. Two simple search terms, ‘Covid’ and ‘mucormycosis’ used to search the entire database in ‘title, abstract, subject’ mode with the search string was tw:(mucormycosis covid). The search was not restricted to any date range.Results: Only 51 reports (40 articles and 01 clinical trials) were obtained with the above search terms. The study found that there is considerable growth in such publication in the last 6 months. Interestingly only three such reports were published in the year 2020. Database wise 38 of these 51 reports were available in Medline. Most of such reports were published by Indian authors. Indian Journal of Ophthalmology emerged as the most productive journal contributing the highest number (10) of these reports.Conclusions: The highly acclaimed publications were the reviews. This study suggests that India is the most productive country for publications related to post-covid mucormycosis. This resembles the fact that the country, faced the excessive emergence of post-covid-19 mucormycosis cases reported the secondhighest number of Covid 19 cases in the substantial worldwide outbreak in the second wave, which is followed by post covid mucormycosis.Bangladesh Journal of Medical Science Vol.20(5) 2021 p.144-147